Recommendations based on the management of patients with Crohn disease in the Peruvian context. Position paper of the Association for the Study of the Intestine (ASPEIN) - Paredes-Méndez, Juan Eloy (2024)
Crohn's disease is a chronic inflammatory disease of the gastrointestinal tract whose etiology is unknown, which can transmurally  affect any segment of the intestine and/or  the perineal region. Worldwide, the incidence  of inflammatory bowel disease has increased in recent decades, and the same upward trend can be seen in South America. At national level, there are no official data, however, the increase in the number of publications in the last 20 years confirms this upward trend. Crohn's disease is a forgotten disease and does not have implemented clinical guidelines based on evidence that contribute to clinicians in decision making. In this sense, the Peruvian Association for the Study of the Intestine considers the preparation of this document relevant and timely. clinical contextualized for Peru.